Fintech: choosing a cloud services provider (2017)
The CIO of Fintech, Inc - a billing-and-payment processing service for the alcoholic beverages industry must choose a cloud services provider for a new application for Fintech's clients. The CIO sees this initiative as a useful first step to take before moving other resources and services into the cloud. His staff briefs him on three providers: Amazon, Google, and Microsoft. Each provider offers services which fit Fintech's requirements, yet with important differences. The Fintech Case from Journal addresses the perspective of a company purchasing cloud computing services, as opposed to a vendor selling cloud computing services. It offers the added benefit of describing an important specialist intermediary in the highly regulated and complex US alcoholic beverages industry.